2019
DOI: 10.3399/bjgpopen19x101661
|View full text |Cite
|
Sign up to set email alerts
|

Response to diagnosis of pre-diabetes in socioeconomically deprived areas: a qualitative study

Abstract: BackgroundDiabetes prevention is a key priority for the NHS, with a particular focus on populations at highest risk. The NHS Diabetes Prevention Programme (NHS DPP) has been introduced, offering a course of dietary and lifestyle education to individuals with pre-diabetes. However, concerns about the NHS DPP include: (1) the possible unintended consequences of labelling more people with a ‘pre-condition’; (2) the possibility of worsening health inequalities as people in socioeconomically deprived areas tend to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Upon receipt of a diagnostic label, 52% of included studies from an individual's perspective reported a need to change their cognitions and emotions. Included studies reported individuals described adaptive (e.g., using humour) and maladaptive (e.g., suicidality) coping mechanisms ( 46 , 48 , 50 , 57 , 61 , 67 69 , 71 , 74 , 82 , 85 , 88 , 98 , 105 , 107 – 109 , 111 , 112 , 114 , 136 , 138 , 139 ), adapting to new condition-specific knowledge ( 62 , 79 , 87 , 88 , 121 ), rejecting negative perceptions ( 50 , 51 , 70 , 104 , 138 ), and accentuating positive elements of the condition ( 51 , 52 , 61 , 86 , 105 , 111 ). These adaptations were reported to be centred around living fulfilling lives post diagnostic labelling ( 70 , 83 , 88 , 107 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon receipt of a diagnostic label, 52% of included studies from an individual's perspective reported a need to change their cognitions and emotions. Included studies reported individuals described adaptive (e.g., using humour) and maladaptive (e.g., suicidality) coping mechanisms ( 46 , 48 , 50 , 57 , 61 , 67 69 , 71 , 74 , 82 , 85 , 88 , 98 , 105 , 107 – 109 , 111 , 112 , 114 , 136 , 138 , 139 ), adapting to new condition-specific knowledge ( 62 , 79 , 87 , 88 , 121 ), rejecting negative perceptions ( 50 , 51 , 70 , 104 , 138 ), and accentuating positive elements of the condition ( 51 , 52 , 61 , 86 , 105 , 111 ). These adaptations were reported to be centred around living fulfilling lives post diagnostic labelling ( 70 , 83 , 88 , 107 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the diagnostic label, individuals in the included studies reported similar, increased , and decreased emotional support . Some individuals reported others became more emotionally and physically distant, either overtly or covertly, and more stigmatising ( 48 , 51 , 56 , 69 , 71 , 73 – 76 , 81 , 88 , 89 , 105 , 107 , 108 , 133 , 134 , 136 , 138 ) following label disclosure, some experienced breakdowns of romantic relationships and marriages ( 52 , 66 , 105 , 107 ), and some perceived a reduction in support from healthcare professionals following diagnostic labelling ( 46 , 56 , 86 , 106 , 132 , 133 , 136 , 139 ). In contrast, others indicated no change or an increase in support from family, friends, and communities, reporting acceptance, tolerance, and strengthened relationships ( 31 , 46 , 48 , 50 , 55 , 57 , 68 , 69 , 73 , 74 , 86 , 91 , 105 , 107 , 113 , 130 , 134 , 138 , 140 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, I thought probably this would not fit me very well because I do exercise on my own … doctors are the subject matter expert. They can give medical advice and tell you what you should do and you take their advice seriously (13) In the midst of the program, if we encounter any problems, health (related) people or at least the doctor might be able to advise us (29).…”
Section: Desire To Have Healthcare Professionals Involved In the Programmentioning
confidence: 99%
“…Regarding lifestyle modifying interventions against T2DM development Gray et al demonstrated that patients from socioeconomically deprived groups were less likely to take up offers of these preventive measures [ 17 ]. In a qualitative study based on semi-structured interviews with 23 prediabetic patients from the most deprived practices of Sheffield (UK) it was showed that personal, social, and environmental factors hindered people to make lifestyle changes [ 18 ]. It is reasonable to suppose that socioeconomic factors may also have a reasonable effect on preventive medication with metformin, but no studies addressing directly this issue can be found.…”
Section: Introductionmentioning
confidence: 99%